HYPOGLYCAEMIC ACTIVITY OF NAUCLEA LATIFOLIA SM. (RUBIACEAE) IN EXPERIMENTAL ANIMALS. - Gidado, A.; Ameh, D. A.; Atawodi, S. E.; Ibrahim, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Aqueous, ethanolic and hexane extracts of the leaves of Nauclea latifolia (Rubiaceae) were assessed for their fasting blood glucose lowering effect in normoglycaemic and streptozotocin – diabetic rats. Wistar strain albino rats were given different doses of the extracts after 18 hrs fast and their blood glucose measured at 0,1,2,4 and 6 hours after treatment. The aqueous and ethanolic extracts significantly lowered the fasting blood glucose levels of the STZ–diabetic rats in a dose–dependent manner. The highest dose administered (400mg/kg) lowered the fasting blood glucose of the diabetic rats by 31.7% (aqueous) and 36.1% (ethanolic) extracts. The aqueous extract did not significantly lower the glucose levels of normoglycaemic rats (maximum 6.6%), nor was any significant decrease seen in the rats administered with the hexane (maximum of 4.0% for normoglycaemic and 2.4% for diabetics) extract. The hypoglycaemic and antihyperglycaemic potentials of the aqueous and ethanolic extracts were comparable to that of glibenclamide (1mg/kg).These results further support the traditional use of the plant in the treatment of diabetes mellitus.